A Sociological Breakthrough of Interreligious Engagement in Everyday-Symbolic Interaction Perspectives - Lattu, Izak (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
This article explores the symbolic interaction, interfaith daily in Indonesia and beyond. The question of how one can live peacefully in a multireligious environment that has colored a discussion about interfaith engagement in many regions of the world. This article begins with a discussion of interfaith relations by introducing the history of migration in Europe. Having developed an awareness of everyday symbolic in migrant-host relationship, this article studied the effect of migration to interfaith engagement in Europe and the United States. Interfaith engagement in this sense is a means of building peace in many parts of the world, including Indonesia. Based on the sociological context of interreligious relations, the article criticized the rigidity of interreligious dialogue is stuck in the official forums related to religious issues. Therefore, religious dialogue based on everyday relationships become important to create the same sphere where everyone has the same solidarity and understanding with all those who have faith and religion are different. [Artikel ini mengeksplorasi interaksi simbolis antariman sehari-hari di Indonesia dan di luar. Pertanyaan bagaimana seseorang dapat hidup secara damai di lingkungan yang multiagama telah mewarnai diskusi tentang keterlibatan lintas agama (interreligious engagement) di banyak wilayah di dunia. Artikel ini dimulai dengan diskusi tentang hubungan antaragama dengan memperkenalkan sejarah migrasi di Eropa. Dengan mengembangkan kesadaran simbolis sehari-hari dalam hubungan migran-tuan rumah, artikel ini mendalami pengaruh migrasi ke keterlibatan antaragama di Eropa dan Amerika Serikat. Keterlibatan antaragama dalam pengertian ini adalah sarana pembangunan perdamaian di banyak bagian dunia, termasuk Indonesia. Berdasarkan konteks sosiologis hubungan antaragama, artikel ini mengkritik kekakuan antaragama yang terjebak dalam forum dialog resmi terkait masalah agama. Oleh karena itu, dialog agama berbasis hubungan sehari-hari menjadi penting untuk menciptakan wilayah yang sama dimana setiap orang memiliki solidaritas dan pemahaman yang sama dengan semua orang yang memiliki iman dan agama yang berbeda